Pterostilbene in the treatment of inflammatory and oncological diseases - Liu, Peijun; Tang, Weihua; Xiang, Kali; Li, Guangcai (Frontiers in Pharmacology, 2024)
Pterostilbene(PTS), a naturally occurring analog of resveratrol(RSV), has garnered significant attention due to its potential therapeutic effects in treating inflammatory and oncological diseases. This comprehensive review elucidates the pharmacological properties, mechanisms of action, and therapeutic potential of PTS. Various studies indicate that PTS exhibits anti-inflammatory, antioxidant, and antitumour properties, potentially making it a promising candidate for clinical applications. Its influence on regulatory pathways like NF-κB and PI3K/Akt underscores its diverse strategies in addressing diseases. Additionally, PTS showcases a favorable pharmacokinetic profile with better oral bioavailability compared to other stilbenoids, thus enhancing its therapeutic potential. Given these findings, there is an increased interest in incorporating PTS into treatment regimens for inflammatory and cancer-related conditions. However, more extensive clinical trials are imperative to establish its safety and efficacy in diverse patient populations.